U.S Audiences' Perceptions of Covid-19 and Conservative News Frames - T. Makana Chock (Coordinamento SIBA, 2020)
During the early stages of the COVID-19 pandemic, U.S. conservative news downplayed the threat of the virus. Perceived risks of COVID-19 are an important factor in influencing citizens' willingness to comply with risk prevention measures. An online survey (N=269) of U.S. residents was conducted March 30 - April 1, 2020. We found that those who used partisan conservative news sources as their primary source of information about the virus were significantly less likely to view it as a threat, compared to those who cited Far Left, Center Left, and Center Right news sources. Politically conservative Far Right news audiences reported significantly lower estimates of their own COVID-19 risk, as well as that of their age group peers, the average person in the U.S., and the average senior citizen in the U.S.